BOOK REVIEWOFLIAN GOUW’SONLY A GIRL - Supatra, Donna Narwastu (LANTERN (Journal on English Language, Culture and Literature), 2013)
In this final project, the writer reviews the novel entitled Only a Girl. The aims of this report are to summarize and describe theme, strengths and weaknesses of Only a Girl. This novel was written by a woman who has had experiences in living in Indonesia during Dutch colonialization until the newly independent Indonesia. The major theme of this novel isthe struggle of Chinese women from three different generations to find out their identity. Besides, this novel also has four minor themes, those are, mother’s love, romances, loyality, and the sruggle of Indonesian people. Setting, character, plot, the author and language translation become the strengths of Only a Girl. On the other hand, no subtitle becomes the weakness of this novel. Only a Girl is an interesting novel because this novel was written or inspired by historical events. This novel is trully recommended for people who love reading remarkable literary works.